The dynamics of households' stock market beliefs - Hans-Martin von Gaudecker; Axel Wogrolly (Center for Economic Studies and ifo Institute (CESifo), 2019)
We analyse a long panel of households' stock market beliefs to gain insights into the nature of their expectations formation processes. We classify respondents into one of five groups based on their data and estimate group-wise models of expectations formation. Two of the groups are at opposite extremes in terms of optimism: Pessimists who expect substantially negative returns and financially sophisticated individuals whose expectations are close to the historical average. Two groups expect returns around zero and differ only in how they respond to information: Extrapolators who become more optimistic following positive information and mean-reverters for whom the opposite is the case. The final group is characterised by poor probability numeracy; its individuals are not willing or able to quantify their beliefs about future returns. None of the estimated belief formation processes passes a rational expectations test.
Keywords: D83; D84; D14; C38; 330; stock market expectations; household finance; heterogeneity; clustering methods